Raised plasma concentrations of α-defensins in patients with idiopathic pulmonary fibrosis. Issue 7 (1st July 2002) - Mukae, H; Iiboshi, H; Nakazato, M; Hiratsuka, T; Tokojima, M; Abe, K; Ashitani, J; Kadota, J; Matsukura, S; Kohno, S
Abstract : Background: Neutrophils are thought to play an important role in the pathogenesis of idiopathic pulmonary fibrosis (IPF). Human neutrophils contain antimicrobial and cytotoxic peptides in the azurophil granules which belong to a family of mammalian neutrophil peptides named α-defensins. A study was undertaken to investigate the role of α-defensins in the pathogenesis of IPF. Methods: The concentrations of α-defensins (human neutrophil peptides (HNPs) 1, 2, and 3) in plasma and bronchoalveolar lavage (BAL) fluid of 30 patients with IPF and 15 healthy subjects were measured by radioimmunoassay. Results: The concentrations of α-defensins in plasma, but not in BAL fluid, were significantly higher in IPF patients than in controls. BAL fluid concentrations of interleukin (IL)-8 in patients with IPF, which were significantly higher than in controls, correlated with those of α-defensins. An inverse relationship was seen between plasma α-defensin levels and the arterial oxygen tension (Pao 2 ) and pulmonary function (vital capacity (%VC), forced expiratory volume in 1 second (FEV1 ), and carbon monoxide transfer factor (%Tlco )) in patients with IPF. Plasma levels of α-defensins also correlated with the clinical course in IPF patients with an acute exacerbation. Immunohistochemically, positive staining was observed inside and outside neutrophils in the alveolar septa, especially in dense fibrotic areas. Conclusion: These findings suggest that α-defensins play an important role in the pathogenesis of IPF, and that the plasma α-defensin level may be a useful marker of disease severity and activity.